Peran Kearifan Lokal dalam Pelestarian Tumbuhan Obat dan Lingkungan di Sumatera Utara - Amrul, Hanifah Mutia Z.N. (Universitas Medan Area, 2024)
Local wisdom represents traditional knowledge passed down through generations and plays a strategic role in the conservation of medicinal plants and the environment. North Sumatra, with its cultural diversity and rich local wisdom, holds significant potential to support environmental conservation. This study aims to explore the role of local wisdom in preserving medicinal plants and the environment through cultural, ecological, and social approaches. The method employed is a descriptive-analytical approach based on literature reviews and case studies from various regions in Indonesia. Several local wisdom practices, such as lubuk larangan, hutan larangan, and the subak system, demonstrate the success of sustainable environmental management. However, challenges such as modernization and globalization threaten cultural values and lead to the homogenization of traditions. Strategies like digitizing local wisdom, integrating it with modern knowledge, and strengthening protective policies are essential to ensure the sustainability of culture and ecosystems. This study emphasizes the importance of harmonizing traditions with contemporary dynamics to achieve more effective conservation efforts.